Analisis Kemampuan Motorik Kasar Siswa Kelas Bawah di Sekolah Dasar - Anung Probo Ismoko (Jurnal Penelitian Pendidikan, 2014)
This research aims at revealing the students’ rough motor ability among lower classes in State Elementary School II Tirip. It is kind of survey research using test and measurement as the data collection techniques. The population of this research were the whole lower classes in the State Elementary School II Tirip to the number of 103 students. Furthermore, the instrument used in this research is rough motor ability tests. Then, data were analyzed using descriptive analysis in the form of percentage by using four categories: very low, low, high, and very high. Based on the research findings, it can be concluded that the rough motor ability of the lower class students is commonly categorized in high. The details of the findings are 4 students or 3.88% of rough motor ability is very low, 27 students or 26.21% of rough motor ability is low, 53 students with the percentage of 51.46% have high rough motor ability, and 19 students or 18:45% of very high rough motor ability. Based on the percentages, students of those having high rough motor ability have higher percentage compared to others, namely 51.46%.